Acute promyelocytic leukemia during pregnancy: a systematic analysis of outcome. Issue 3 (3rd March 2016) - Verma, Vivek; Giri, Smith; Manandhar, Samyak; Pathak, Ranjan; Bhatt, Vijaya Raj
Abstract : The outcomes of acute promyelocytic leukemia (APL) in pregnancy are largely unknown. The MEDLINE database was systematically searched to obtain 43 articles with 71 patients with new-onset APL during pregnancy. Induction therapy included various regimens of all-trans retinoic acid (ATRA), cytarabine, and anthracycline and resulted in a complete remission rate of 93%. Obstetric and fetal complications included pre-term deliveries (46%), spontaneous/therapeutic abortion/intrauterine death (33.3%) and other neonatal complications (25.9%). Mothers diagnosed in the first trimester were more likely to experience obstetric ( p < 0.01) and fetal ( p < 0.01) complications. To our knowledge, this is the largest systematic review of APL in pregnancy. The vast majority of APL patients in pregnancy may achieve remission with initial induction therapy. APL or its therapy in pregnancy, however, is associated with a high risk of fetal and obstetrical complications. The results of our study may help in patient counseling and informed decision-making.